Membaca peta ekonomi Indonesia : analisis data makroekonomi dan implikasinya bagi kebijakan publik - Hanik, Ummi (Maliki Interdisciplinary Journal, 2025)
Abstract. The Indonesian economic map is a map that present econonomic data in Indonesian in a geography cpntecs. The Indonesian economic map can show several things, namely activities, patterns and distribution in various regions in Indonesia. Therefore, studying the Indonesian Ekonomic Map is very important for people’s lives, which aims to analyze the latest macroeconomics ana identifity the implications that have an impact on public policy in order to gain a better understanding of the state of the Indonesian economy. Thus research provides a comprehensive overview of Indonesia’s current economic growth, obstacles and some of the opertunities that currently exist looking at indicators such as trade balance investment, inflation levels, unemployment an GDP. This research method includes descriptive analysis methods and econometric approaches to evaluate the relationship between main macroeconomic variabels. The result of the research analysis show that domestic factor such as fluctuations in commodity prices thourghhout the world and global economic dynamics can influennc indonesia’s economic growth. To encourage sustainable economic growth, there must be strengthening themanufacturing economic sector, economic diversication, increasing fiscal efficiency, and efforts to stabilize inflation. These factors are all very important according to the policy implications that have ben made. It is hopes that this study will be a motivation for Indonesia’s economic progress in the future, because Indonesia has a mixed economic system that includes various personal freedom and is cpmbined with centralized economic planning and government regulations.